Finite element parametric study of the influence of friction pad material and morphological characteristics on disc brake vibration phenomena. (September 2016) - Forte, P; Frendo, F; Rodrigues, R N
Abstract: Since nowadays the NVH performance of vehicles has become an important priority, the noise radiating from brakes is considered a source of considerable passenger discomfort and dissatisfaction. Creep groan and squeal that show up with annoying vibrations and noise in specific frequency ranges are typical examples of self-excited brake vibrations caused by the stick-slip effect, the former, by the mode coupling of brake disc and friction pads or calliper, the latter. In both cases, the friction coefficient, which depends, among other factors, on the morphology of the mating surfaces and on the operating conditions, is a fundamental parameter but not the only one for the occurrence of the vibratory phenomena. Finite element complex eigenvalue parametric analyses were performed on a disc brake assembly to evaluate propensity to dynamic instability of brakes with multiple pads, as in railway brakes, as a function of the number of pads, pad shape and size, and material parameters.